Proses Pembelajaran dengan Menggunakan Pendekatan Student Centered Approach - Juhra, Al (Pencerah, 2024)
The Student-Centered Approach is one of the effective approaches in modern learning, because learning is a process of comprehensive change in the individual, including cognitive, psychomotor, and affective aspects obtained through information, knowledge, and daily experiences. An effective learning process must be designed to be interactive, inspiring, challenging, fun, and able to motivate students to be active. This is in line with the goal of National Education in the National Education System Law No. 20 of 2003, which is to develop the potential of students to become human beings of faith, piety, noble character, creativity, and independence. This study aims to analyze the effectiveness of the Student-Centered Approach in improving student learning outcomes, explore the challenges and opportunities for its implementation, and provide recommendations for the development of this approach-based learning. The research method used is descriptive with a qualitative approach based on literature review. Data was obtained through analysis of relevant literature, such as books, journals, and academic articles that discuss the implementation and effectiveness of the Student-Centered Approach. The data was analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that this approach can improve student engagement, critical thinking skills, and creativity. This approach can be optimized through methods such as Project-Based Learning, Problem-Based Learning, and Discovery Learning. With the right implementation, the Student-Centered Approach has the potential to support learning success in various modern educational contexts.